The choosing of school principals and its relationship to the principle of democratic management in public education in municipalities of Paraná - Simone de Fátima Flach (Universidade Federal de Santa Catarina, 2019)
From documentary research, focusing on legislation and normative documents, this text analyzes the forms of designation of directors of public schools in municipalities in the state of Paraná that have already instituted their own teaching systems, aiming at pointing out possibilities and limits for the implementation of the principle of democratic management from community participation. The theoretical framework that supports the analyzes is the historical and dialectical materialism, especially Antonio Gramsci's thinking, which helps understand the experience of democracy as a possibility of individual freedom with collective commitment. It is concluded that the process of choosing school principals in the municipalities investigated presents conservative remnants, even when it points to the broad participation of the community in an elective process, and that the implementation of the principle of democratic management is one of the means for the formation of a collective conscience that has freedom as an end.